Age-dependent changes of baroreflex efficiency in Dahl rats: effects of high salt intake - Nedvídek, J; Zicha, J (Physiological research, 1993)
The age-dependent changes in baroreflex control of heart rate were studied in inbred Dahl rats. At the age of 8 weeks the baroreflex slope was significantly greater in salt-resistant (R/Jr) than in salt-sensitive (S/Jr) rats fed a low-salt diet. The reverse was true in 16-week-old animals. High salt intake (8% NaCl diet for 4 weeks) suppressed baroreflex efficiency in both age groups of S/Jr animals whereas no effects occurred in R/Jr rats. Baroreflex slope was, however, significantly lower in young S/Jr rats with a severe form of salt hypertension than in adult salt-loaded S/Jr rats in which only a moderate blood pressure elevation was observed.
Keywords: Male; Aging; Rats, Inbred Strains; Genotype; Heart Rate; Baroreflex; mužské pohlaví; srdeční frekvence; inbrední kmeny potkanů; Sodium, Dietary; krysa rodu Rattus; Animals; sodík dietní; krevní tlak; zvířata; Rats; Blood Pressure; stárnutí; genotyp; Phenylephrine; baroreflex; fenylefrin